Revitalizing Student Activism for Strengthening Religious Moderation in Islamic Higher Education Institutions - Habibah, Ummu; Djam'annuri, Djam'annuri; Mulyo, A. Mufrod Teguh (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
This study aims to analyze the implementation of strengthening religious moderation through student development at UIN Kiai Ageng Muhammad Besari Ponorogo. The research uses a qualitative approach with a case study type in the 2021–2025 period. Data were obtained from primary sources in the form of interviews with leaders, lecturers, and students, as well as secondary sources in the form of institutional documents. Data collection techniques included observation, in-depth interviews, and documentation, while data analysis used the Miles and Huberman model through reduction, presentation, and conclusion drawn. The results of the study showed that strengthening religious moderation was carried out through an integrated strategy based on three pillars, namely intracurricular, cocurricular, and extracurricular. This integration is reflected in the curriculum, thematic activities of the Religious Moderation House, and student activism through student organizations. These findings show that an integrated approach is effective in forming an inclusive and tolerant attitude of religiosity. This study concludes that integration-based student development is a key strategy in strengthening religious moderation, although it still requires further development to be widely adapted.